Phylogenetic biogeography of Aristolochiaceae s. l. - Kandidov , M. V.; Iovlev, P. S. (Проблемы ботаники Южной Сибири и Монголии, 2020)
The original molecular data analyses of 28 species from different genera of Aristolochiaceae s. l. familywas analyzed. As a result, the cladogram was built, and it formed the basis for compiling maps of the correlation ofphylogenetic relationships and modern areals of species from Aristolochiaceae s. l. family, which were chosen for analysis.